Analysis of Diet Pattern Ability Setting in Hypertension Patients with Self-Care Theory Approach - Fikriana, Riza; Nurbadriyah, Wiwit Dwi; Kodriyah, Lailatul; Rosalina, Rosalina (International Journal of Psychosocial Rehabilitation, 2020)
The number of Patients with hypertension continues to increase every year. Hypertension is often referred to as " The Silent Killer " disease. The ability to regulate dietary patterns to prevent complications is needed. The purpose of this study was to analyze the ability to regulate dietary patterns in patients with hypertension. The design of this research was analytic observational with a cross-sectional approach. Samples were taken using a purposive sampling technique resulting in 92 respondents. Inclusion criteria are people with hypertension in Tegalsari Village, Kepanjen, Malang who are willing to be respondents and the exclusion criterion is a mental disorder. This study using a closed questionnaire (list of questions with answers provided by the researcher) which includes knowledge, attitude, health worker support and an ability questionnaire (regulation of dietary patterns for hypertension sufferers). Statistical tests used multiple linear regression analysis tests. The results of the multiple linear regression analysis test found that from the variables knowledge, attitude, support of health workers the attitude variable had the biggest influence on the ability to regulate dietary patterns with a significance value ( p-value: <0.001), followed by knowledge (p-value: 0.227) and support of health workers (p-value: 0.969). Attitude is the most important factor that can influence the ability to regulate dietary patterns, so it is necessary to increase a positive attitude in someone to improve the ability to regulate diet and to prevent an increase in uncontrolled blood pressure or hypertension complications.